2020
DOI: 10.2196/22108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Utility of Smartphone-Based Sensor Assessments in Persons With Multiple Sclerosis in the Real-World Using an App (elevateMS): Observational, Prospective Pilot Digital Health Study

Abstract: Background Multiple sclerosis (MS) is a chronic neurodegenerative disease. Current monitoring practices predominantly rely on brief and infrequent assessments, which may not be representative of the real-world patient experience. Smartphone technology provides an opportunity to assess people’s daily-lived experience of MS on a frequent, regular basis outside of episodic clinical evaluations. Objective The objectives of this study were to evaluate the fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 58 publications
1
80
0
2
Order By: Relevance
“…Pratap et al in a large study including more than 500 pwMS described that ElevateMS can be used to longitudinally (12 weeks period) collect formation about the most common symptoms of MS. During this follow-up, they observed that the most frequent complaints are fatigue (63%), memory issues (42%) and difficulty with walking (41%). After the intervention, there were significant increased functional performances and QoL [59]. To summarize the findings of this study we listed the different mHealth according to the targeted ICF domain for both rehabilitation and self-assessment in Table 3.…”
Section: Self-assessmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Pratap et al in a large study including more than 500 pwMS described that ElevateMS can be used to longitudinally (12 weeks period) collect formation about the most common symptoms of MS. During this follow-up, they observed that the most frequent complaints are fatigue (63%), memory issues (42%) and difficulty with walking (41%). After the intervention, there were significant increased functional performances and QoL [59]. To summarize the findings of this study we listed the different mHealth according to the targeted ICF domain for both rehabilitation and self-assessment in Table 3.…”
Section: Self-assessmentmentioning
confidence: 98%
“…Concerning the self-assessment tools six studies, using 6 different mHealth applications, have been included in the review, representing 1,129 participants (955 pwMS [88% with RRMS, 5% with SPMS and 7% with PPMS, average EDSS 2.50.5] and 174 healthy participants) [54][55][56][57][58][59]. The characteristics of the studies and participants are summarized in Table 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also the most common debilitating neurological disorder in adults. Not only MS is regarded as a serious health problem but also its economic burden in terms of the costs associated with the patient care and treatments as well as patients' reduced economic activities have received more attention in the past years [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Auch wenn sich Patienten an die anfängliche Symptomzunahme zunächst gewöhnen [26] oder sich diese als tagesabhängige Variation erklären [27], so nehmen sie doch sehr genau wahr, wie insbesondere die funktionalen Defizite und Einschränkungen des täglichen Lebens zunehmen [28]. Verschiedene Softwarelösungen und Smartphone Applikationen wie die Floodlight Testbatterie [29], der MS-CoPilot [30], elevateMS [31] oder der Open MS BioScreen [32] ermöglichen MS-Patienten ein kontinuierliches Selbst-Monitoring, um die Zunahme körperlicher und kognitiver Einschränkungen in der Alltagssituation zu erfassen. Um eine mögliche SPMS-Konversion frühzeitig anamnetisch detektieren zu können [33], müssen jedoch Patient und Neurologe in der Lage sein, die frühen Hinwei-se und oft unklaren Anzeichen während der regulären Visite zu kommunizieren bzw.…”
Section: Introductionunclassified